Preparation method of high-tension lightweight concrete and lightweight concrete

Through the combination of modified coal gangue ceramide and plant protein foaming agent, the compressive strength and fluidity of lightweight concrete are improved, and the problems of low compressive strength and large slurry loss of lightweight concrete in construction projects are solved. Achieve higher mechanical properties and application efficiency.

CN119241144AActive Publication Date: 2025-01-03SHANGHAI CONSTR BUILDING MATERIALS TECH GRP CO LTD +1

Patent Information

Application Number
CN202411264091.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-03
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

Lightweight concrete has low compressive strength in construction projects, which leads to prone to cracking and seepage of insulation, and there are problems of large slurry loss and low mechanical strength in application of formwork without removal.

Method used

Using the high-tension lightweight concrete preparation method, by mixing coal gangue ceratops, cement, foaming agent, inorganic salts and polyvinyl alcohol in a specific proportion, and using the modified liquid through heating and soaking steps, combined with soap A kerato-glycemic plant protein foaming agent improves the compressive strength and fluidity of concrete and reduces slurry loss.

Benefits of technology

The compressive strength of lightweight concrete is improved, allowing it to withstand more gravity loads of mechanical equipment, reduce slurry loss and loss in disassembly-free formwork applications, and enhance the mechanical properties of building insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005036642730000031
    Figure BDA0005036642730000031
  • Figure BDA0005036642730000041
    Figure BDA0005036642730000041
  • Figure BDA0005036642730000042
    Figure BDA0005036642730000042
Patent Text Reader

Abstract

The invention relates to a high-tension lightweight concrete preparation method and lightweight concrete. 800-1200 parts by weight of coal gangue ceramsite, 420-500 parts by weight of cement, 240-450 parts by weight of water, 0.5-1.5 parts by weight of a foaming agent, 2-4 parts by weight of inorganic salt, 2-4 parts by weight of polyvinyl alcohol and 0.2 part by weight of a water-based dispersant are taken, the polyvinyl alcohol and the water-based dispersant are immersed in the water and then heated, and a modified solution is obtained; the preparation method comprises the following steps: soaking coal gangue ceramsite in a modification liquid to obtain a mixed material A containing modified coal gangue ceramsite; cement and inorganic salt are mixed and stirred to be evenly mixed, and a mixed material B is obtained; the foaming agent is diluted and then foamed through foaming equipment to generate foam; the mixed material A and the mixed material B are mixed and stirred, foam generated by foaming of the foaming agent is filled in the stirring process, stirring continues to be conducted for 1-2 min, and the lightweight concrete is obtained. By modifying the coal gangue ceramsite, the coal gangue ceramsite can slowly release an ion additive and part of water, so that a chemical reaction is fully carried out, and the compressive strength is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a method for preparing high-tension lightweight concrete and lightweight concrete. Background Art

[0002] Lightweight concrete, also known as foamed concrete, is a building material formed by introducing tiny closed bubbles into the slurry through chemical or physical foaming. It has good lightness, thermal insulation, fire resistance and sound insulation, and can reduce construction procedures, speed up construction progress and reduce project costs.

[0003] In the field of construction engineering, lightweight concrete can be applied to integrated non-disassembly formwork for building structure insulation and prefabricated assembled insulation wall panels.

[0004] The building insulation layer generally has the problem of low compressive strength, especially the early compressive strength of lightweight concrete. During daily maintenance, the insulation layer cracks and leaks due to equipment handling and personnel activities. In addition, the insulation layer used as indoor partition walls is also unable to install equipment on the wall due to its low strength.

[0005] The integrated non-removal formwork is lighter than the traditional casting formwork. Common non-removal formwork is represented by wire mesh membrane. Conventional foam concrete has problems such as large slurry loss, low mechanical strength, and labor-intensive surface roughening during the application of non-removal wire mesh membrane. Summary of the invention

[0006] In order to solve the problems of low compressive strength of existing lightweight concrete and large loss caused by loss on wire mesh membrane materials, the present invention provides a high-tension lightweight concrete preparation method and lightweight concrete, which increases the compressive strength of lightweight concrete while reducing losses when used in integrated non-disassembly formwork.

[0007] The technical objectives of the present invention are achieved through the following technical solutions:

[0008] A method for preparing high-tension lightweight concrete, comprising taking 800-1200 parts of coal gangue ceramsite, 420-500 parts of cement, 240-450 parts of water, 0.5-1.5 parts of foaming agent, 2-4 parts of inorganic salt, 2-4 parts of polyvinyl alcohol, and 0.2 parts of aqueous dispersant according to the weight ratio, the method comprising:

[0009] Step 1, immersing polyvinyl alcohol and an aqueous dispersant in water and then heating them to obtain a modified liquid;

[0010] Step 2, soaking the gangue ceramsite in a modification liquid to obtain a mixed material A containing modified gangue ceramsite;

[0011] Step 3, mixing cement and inorganic salt to make them uniformly mixed to obtain a mixed material B;

[0012] Step 4, diluting the foaming agent and foaming it through a foaming device to generate foam;

[0013] Step 4: Mix material A and material B and stir them. During the stirring process, add the foam generated by the foaming agent and continue stirring for 1-2 minutes.

[0014] Furthermore, the coal gangue ceramsite has an apparent density of 1700 kg / m 3 The following are coal gangue ceramsite with fineness modulus of 1.9-2.6, particle size of 0.15-5mm, water absorption of 5-15%, and cylinder pressure strength of 10-15MPa.

[0015] Furthermore, during heating in step 1, the water temperature is heated to no more than 60° C., and the water is heated until the polyvinyl alcohol and the aqueous dispersant are completely dissolved in the water.

[0016] Furthermore, in step 2, the soaking time of the gangue ceramsite is controlled within 5-10 minutes.

[0017] Furthermore, it also includes adding silica fume and / or fly ash to replace 10%-20% of cement.

[0018] Furthermore, the specific surface area of ​​the silica ash is above 23000 m2 / kg, and the silica acid content in the silica ash is greater than 75%; and the mineral powder is at least one of S95 mineral powder and S105 mineral powder.

[0019] Furthermore, the foaming agent is a saponin-type plant protein foaming agent.

[0020] Furthermore, the inorganic salt is at least one of calcium sulfate and sodium thiosulfate.

[0021] The present invention also provides a high-tension lightweight concrete, comprising coal gangue ceramsite, cement, water, foaming agent, inorganic salt, polyvinyl alcohol and aqueous dispersant, which is prepared by the coal gangue ceramsite, cement, water, foaming agent, inorganic salt, polyvinyl alcohol and aqueous dispersant according to the above-mentioned preparation method.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The lightweight concrete prepared by the method of the present invention, through the modification of coal gangue ceramsite, allows the coal gangue ceramsite to adsorb ion additives. During the hardening process of concrete, the coal gangue ceramsite slowly releases the ion additives and part of the water to allow the chemical reaction to proceed fully, thereby improving the interface strength between the aggregate and the slurry, and the compressive strength can reach more than 10MPa. Compared with the existing foam concrete and polystyrene particle concrete, it can withstand more gravity loads of mechanical equipment.

[0024] 2. The high-tension lightweight concrete of the present invention, under the premise of ensuring good fluidity, makes it difficult for the concrete slurry to leak due to the surface tension due to the addition of surfactants, thus solving the problem of slurry loss and large loss during the application of steel mesh membrane in the existing foam concrete.

[0025] 3. The foaming agent of the present invention adopts a saponin-type plant protein foaming agent, which has a simple production process and is not sensitive to hard water rich in calcium ions, thereby ensuring that the performance of the foaming agent will not be affected by changes in water quality. If necessary, a mixing station can be used to recycle water, which is beneficial to environmental protection. In addition, as a plant-based foaming agent, it has a small odor. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described below in conjunction with specific embodiments:

[0027] Example 1

[0028] According to the weight ratio, 1200 parts of coal gangue ceramsite, 420 parts of cement, 1.5 parts of foaming agent and 360 parts of water are taken; among which, the apparent density of coal gangue ceramsite is 1700kg / m 3 The following is the coal gangue ceramsite with fineness modulus of 1.9-2.6, particle size of 0.15-5mm, water absorption of 5-15%, and cylinder pressure strength of 10-15MPa; the foaming agent is saponin type plant protein foaming agent.

[0029] The gangue ceramsite, cement and water are mixed and stirred, and the foam produced by the foaming agent is added and stirred evenly to obtain lightweight concrete. The various performance parameters of the lightweight concrete are tested, as shown in the following table:

[0030]

[0031]

[0032] Example 2

[0033] A method for preparing high-tension lightweight concrete, comprising taking 1200 parts of coal gangue ceramsite, 420 parts of cement, 360 parts of water, 1.5 parts of foaming agent, 2 parts of calcium sulfate, 2 parts of polyvinyl alcohol, and 0.2 parts of water-based dispersant according to the weight ratio, wherein the water-based dispersant is sodium polyacrylate;

[0034] Among them, the apparent density of coal gangue ceramsite is 1700kg / m 3 The following coal gangue ceramsite has a fineness modulus of 1.9-2.6, a particle size of 0.15-5mm, a water absorption rate of 5-15%, and a cylinder pressure strength of 10-15MPa;

[0035] The foaming agent is a saponin type plant protein foaming agent.

[0036] The production process includes the following steps:

[0037] Step 1, immersing polyvinyl alcohol and sodium polyacrylate in water and then heating them to obtain a modified solution;

[0038] Step 2, soaking the gangue ceramsite in the modification liquid, and strictly controlling the soaking time within 5-10 minutes to obtain a mixed material A containing the modified gangue ceramsite;

[0039] Step 3, mixing cement and calcium sulfate to obtain a mixed material B;

[0040] Step 4, diluting the foaming agent and foaming it through a foaming device to generate foam;

[0041] Step 4: Mix the mixed material A and the mixed material B and stir them. During the stirring process, the foam generated by the foaming agent is added and the stirring is continued for 1-2 minutes to obtain a lightweight concrete. The various performance parameters of the lightweight concrete are tested, as shown in the following table:

[0042]

[0043] Example 3

[0044] A method for preparing high-tension lightweight concrete comprises the following steps: taking 800 parts of coal gangue ceramsite, 420 parts of cement, 360 parts of water, 1.5 parts of foaming agent, 2 parts of calcium sulfate, 2 parts of polyvinyl alcohol, and 0.2 parts of aqueous dispersant according to the weight ratio, wherein the aqueous dispersant is sodium polyacrylate.

[0045] Among them, the apparent density of coal gangue ceramsite is 1700kg / m 3 The following coal gangue ceramsite has a fineness modulus of 1.9-2.6, a particle size of 0.15-5mm, a water absorption rate of 5-15%, and a cylinder pressure strength of 10-15MPa;

[0046] The foaming agent is a saponin type vegetable protein foaming agent.

[0047] The preparation comprises the following steps:

[0048] Step 1, immersing polyvinyl alcohol and sodium polyacrylate in water and then heating them to obtain a modified solution;

[0049] Step 2, soaking the gangue ceramsite in the modification liquid, and strictly controlling the soaking time within 5-10 minutes to obtain a mixed material A containing the modified gangue ceramsite;

[0050] Step 3, mixing cement and calcium sulfate to obtain a mixed material B;

[0051] Step 4, diluting the foaming agent and foaming it through a foaming device to generate foam;

[0052] Step 4: Mix the mixed material A and the mixed material B and stir them. During the stirring process, the foam generated by the foaming agent is added and the stirring is continued for 1-2 minutes to obtain a lightweight concrete. The various performance parameters of the lightweight concrete are tested, as shown in the following table:

[0053]

[0054] Example 4

[0055] On the basis of Example 3, silica fume and / or mineral powder are added to replace 10%-20% of the cement dosage to improve the mechanical properties of concrete. A method for preparing high-tension lightweight concrete, according to the weight ratio, takes 800 parts of coal gangue ceramsite, 340 parts of cement, 30 parts of silica fume, 50 parts of mineral powder, 360 parts of water, 1.5 parts of foaming agent, 2 parts of calcium sulfate, 2 parts of polyvinyl alcohol, and 0.2 parts of water-based dispersant, wherein the water-based dispersant is sodium polyacrylate.

[0056] Among them, the apparent density of coal gangue ceramsite is 1700kg / m 3 The following coal gangue ceramsite has a fineness modulus of 1.9-2.6, a particle size of 0.15-5mm, a water absorption rate of 5-15%, and a cylinder pressure strength of 10-15MPa;

[0057] The foaming agent is a saponin type plant protein foaming agent.

[0058] The preparation comprises the following steps:

[0059] Step 1, immersing polyvinyl alcohol and sodium polyacrylate in water and then heating them to obtain a modified solution;

[0060] Step 2: soak the gangue ceramsite in the modification liquid for 5-10 minutes to obtain a mixed material A containing the modified gangue ceramsite;

[0061] Step 3, mixing cement and calcium sulfate to obtain a mixed material B;

[0062] Step 4, diluting the foaming agent and foaming it through a foaming device to generate foam;

[0063] Step 4: Mix the mixed material A and the mixed material B and stir them. During the stirring process, the foam generated by the foaming agent is added and the stirring is continued for 1-2 minutes to obtain a lightweight concrete. The various performance parameters of the lightweight concrete are tested, as shown in the following table:

[0064]

[0065] It can be seen from Examples 1-4 that sulfate and polyvinyl alcohol in the mix ratio, as dispersants and surfactants, increase the contact angle of cement paste, that is, the surface tension of the liquid increases, and the liquid is not easy to spread on the solid surface. While improving the concrete wrapping, the slurry loss during the construction process is reduced, that is, the liquid overflowing from the grid is reduced. In addition, since the insulation layer is a non-structural part and does not come into contact with steel bars, etc., it will not rust, and a small amount of sulfate does not have a significant effect on the mechanical properties of high-tension lightweight concrete.

[0066] Since concrete with a low water-binder ratio may not be fully hydrated, the working performance of high-tension lightweight concrete can be changed to a certain extent by adjusting the slurry-binder ratio. The modified gangue ceramsite slowly releases the water and ion additives stored in the pre-wetting process. The water and chemical substances stored in the gangue ceramsite are slowly released during the concrete forming process. On the one hand, it participates in the hydration reaction of cement particles and improves the strength of concrete; on the other hand, it provides moisture to reduce foam loss and reduce the dry bulk density of the finished concrete. It plays an internal curing role on the cement paste and improves the mechanical properties of concrete. It solves the problem of easy leakage and large loss of lightweight concrete in the application of formwork removal, and has a wider application prospect in construction fields such as building insulation layer.

[0067] This embodiment is only a further explanation of the present invention, not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to this embodiment as needed, but as long as it is within the scope of the claims of the present invention, it will be protected by the patent law.

Claims

1. A method for preparing high-tension lightweight concrete, characterized in that: According to the weight ratio, 800-1200 parts of coal gangue ceramsite, 420-500 parts of cement, 240-450 parts of water, 0.5-1.5 parts of foaming agent, 2-4 parts of inorganic salt, 2-4 parts of polyvinyl alcohol, and 0.2 parts of aqueous dispersant are taken. The method comprises: Step 1, immersing polyvinyl alcohol and an aqueous dispersant in water and then heating them to obtain a modified liquid; Step 2, soaking the gangue ceramsite in a modification liquid to obtain a mixed material A containing modified gangue ceramsite; Step 3, mixing cement and inorganic salt to make them uniformly mixed to obtain a mixed material B; Step 4, diluting the foaming agent and foaming it through a foaming device to generate foam; Step 4: Mix material A and material B and stir them. During the stirring process, add the foam generated by the foaming agent and continue stirring for 1-2 minutes.

2. A method for preparing high-tension lightweight concrete according to claim 1, characterized in that: The coal gangue ceramsite has an apparent density of 1700 kg / m 3 The following are coal gangue ceramsite with fineness modulus of 1.9-2.6, particle size of 0.15-5mm, water absorption of 5-15%, and cylinder pressure strength of 10-15MPa.

3. The method for preparing high-tension lightweight concrete according to claim 1, characterized in that: During the heating in step 1, the water temperature is heated to no more than 60° C., and the water is heated until the polyvinyl alcohol and the aqueous dispersant are completely dissolved in the water.

4. The method for preparing high-tension lightweight concrete according to claim 1, characterized in that: In step 2, the soaking time of the gangue ceramsite is controlled to be 5-10 minutes.

5. The method for preparing high-tension lightweight concrete according to claim 1, characterized in that: The method further comprises adding silica fume and / or fly ash in an equal amount to replace 10% to 20% of the cement.

6. The method for preparing high-tension lightweight concrete according to claim 1, characterized in that: The specific surface area of ​​the silica ash is above 23000 m2 / kg, and the silica acid content in the silica ash is greater than 75%; the mineral powder is at least one of S95 mineral powder and S105 mineral powder.

7. The method for preparing high-tension lightweight concrete according to claim 1, characterized in that: The foaming agent is a saponin type plant protein foaming agent.

8. The method for preparing high-tension lightweight concrete according to claim 1, characterized in that: The inorganic salt is at least one of calcium sulfate and sodium thiosulfate.

9. A high-tension lightweight concrete, characterized in that: The invention comprises coal gangue ceramsite, cement, water, foaming agent, inorganic salt, polyvinyl alcohol and aqueous dispersant, which are prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Low-shrinkage sludge ceramsite alkali-activated full-slag foam concrete plate and preparation method thereof

    CN104230280A

  • Ceramsite foam concrete and preparation process thereof

    CN110054451A

  • Lightweight recycled concrete and preparation method thereof

    CN114195443A

  • Manufacturing method of concrete molding, and concrete molding

    JP2007261119A

  • Ultralight inorganic foam and manufacture method thereof

    WO2017085416A1

Cited By

  • Concrete for light curtain wall and preparation method thereof

    CN121494421A